Memur disiplin hukukunun genel ilkeleri - Orman, Harun (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Kamu Hukuku Anabilim Dalı / Kamu Hukuku Bilim Dalı, 2011)
Kamu hizmeti, toplum düzeninin içinde ayrı bir düzenlemeye ihtiyaç gösteren özel bir alandır. Kendine özgü kurumları ve kuralları vardır. Hedefi toplumsal düzenin işlemeyen yönlerini tamir ederek topluma düzen getirmek olan hukukun toplum düzenini sağlayan ceza kuralları kamu hizmeti düzenini koruma için yeterli değildir. Kamu hizmetinin aksamadan işlemesi için ayrı kurallara ihtiyaç vardır. Kamu hizmetinin aksamasına sebebiyet veren kamu görevlilerinin hangi davranışlarının hangi disiplin cezasını gerektirdiğini belirleyen, kamu hizmetlerinin etkin bir biçimde görülmesini sağlayan, disiplin suçlarını ve cezalarını belirleyerek çeşitli idari yaptırım ve ödüller ile bunların uygulanmasına ilişkin kuralları koyan disiplin hukukuna ilişkin mevzuat çeşitliliği, mevzuatla tanınan takdir yetkileri ve mevzuatın güncel olmaması gibi hususlar disiplin cezalarının muhataplarını bazen haksız yere mağdur edebilmektedir. Kamu görevlilerinin kariyerinde ve özlük haklarında kısıtlamalar, görevine son verilmesi gibi neticeler içeren disiplin cezalarının bu denli önemli sonuçları ve niteliği gereği, uygulanırken kanunlarda öngörülen esas ve usullere riayet edilmesi bazen yeterli olmamaktadır. Bu yaptırımların uygulayıcıları, mevzuatta tanınan yetkileri kullanılırken, mağduriyetlere neden olunmaması, disiplin cezalarının amacına hizmet edebilmesi ve disiplin cezalarının tehdit aracı olarak kullanılmasının önüne geçilmesi için ceza hukukuna ilişkin hukukun genel ilkelerinden kaynaklanan temel esasları, uluslararası anlaşmalardan kaynaklanan yükümlülükleri, yargı kararları ile ortaya konulmuş içtihatları ve yargı mercilerince verilen kararlarda genel kabul görmüş doktrin ve prensipleri dikkate almak zorundadırlar. Bu durum hukuk devleti olmanın bir gereğidir. Bu çalışmada disiplin cezalarının önemli sonuçlarından dolayı ve cezaların amacına hizmet etmesi, idarecilerin maiyetindeki memurlar üzerinde baskı unsuru olarak kullanmasının önüne geçilebilmesi için, uygulayıcıların dikkat etmesi gereken usul, esas ve ilkeler örnek yargı kararları ile birlikte incelenecektir.

Public services, as a special sphere of concept of the public order, need to be regulated with different rules then general principles for maintenance of public order. Public services have a lot of norms and mechanismas pertain to its own unique fıeld. Criminal rules and punishments are part of the public law which ensure public order and safety and very effective indeed but they are not enough, or sole material for this purpose. Achieving highest standarts of public peace and order authorities need to use other rules and norms beside criminal ones. Disciplinary acts and actions are being used against public servants who disturb intra-instutional order. Disciplinary rules indicate that which actions and deeds are disciplinal erime and must be punished by disciplinary punishments. Using this kind of punishments authorities ensure intra-institutional order. Standards of public services will be elevated by using this kind of methods. For institutional integrity and harmony will be achieved only by doing this. Disciplinary law regulates this fıeld and states that which kind of actions are disciplinal erime, in which way they will be punished, what is the disciplinal offense, what are the main instruments for proteetion of the potantial culprit's fundamental basic rights, vvhat are the essential rules and norms which govern this fıeld. Vast number of laws and regulations at this topic, its variety, ignorance about protectional mechanisms, being outdated, misusage by administrators for ali these reasons, sometimes disciplinal punishments put individuals in aggrieved stuation and make them vietim instead of ensuring public order. Disciplinary penalties are sometimes very grave indeed. Expelling from the duty, cutting monetary rights, hindering career advancement are some of them. Sometimes laws and regulations, statutory materials are not suffıcient to protect individuals from rights' violations. Very fundamental aspect of the state is the rule of law. This principle must be prevalent at ali level of administration.General principles of law, commitments stemming from international agreements, case law at this fıeld, court decisions, general accepted doctirinal principles must be taken into consideration at the evaluation of the stuation at hand. Individual proteetion against arbitrary, unlawfull act and action can only be ensured by this kind of comprehensive look. In this study, fundamental norms and principles at this topic, main protectional instruments against abuse of power wested in authorities, disciplinal offenses, procedural methods are being examined.
The general principles of law in the disciplinary officer
Keywords: Hukuk; Kamu Yönetimi; Disiplin; Disiplin Cezaları; Disiplin Yönetmeliği; Kamu Hukuku; Kamu Personeli; Memurlar; Law; Public Administration; Discipline; Disciplinary Punishments; Disciplinary regulations; Public Law; Public Personnel; Civil Servants